The Impact of Covid-19 Pandemic on Hidradenitis Suppurativa Patients: a Cross-Sectional Study From Tertiary Referral Hospital - Ecem Bostan; Adam Jarbou; Aysen Karaduman; Duygu Gulseren; Neslihan Akdogan; Basak Yalici-armagan (Mattioli1885, 2022)
Introduction: Hidradenitis suppurativa (HS) is a chronic, disabling skin disorder which is characterized by recurrent attacks of nodule, abscess, sinus tract formation which eventually leads to significant scarring. Oral/topical antibiotics, oral retinoids and TNF-alpha inhibitors are used to control disease activity and improve symptoms.   Objective: In the present study, we aimed to determine the prevalance of COVID-19 real-time polymerase chain reaction (RT-PCR) positivity and Covid-19 related symptoms in relation to the age, gender, body mass index (BMI), disease duration, accompanying systemic diseases, treatment used for HS, treatment duration and smoking.   Methods: We conducted a comparative, cross-sectional study of 178 patients diagnosed with HS in a referral hospital. Age, gender, smoking status, BMI, treatment modalities used for HS, the presence of COVID-19 related symptoms, history of close contact to a person with COVID-19 and COVID-19 RT-PCR results were determined by a telephone questionnaire and checked from medical data records.   Results: Sixty-three patients were female, whereas 115 patients were male. During Covid-19 pandemic, 94 out of 178 patients had Covid-19 related symptoms; Covid-19 RT-PCR test was performed in 109 (61.2%) patients. Thirty (27.5%) cases tested positive for Covid-19 whereas 79 (72.5%) tested negative.   Conclusions: Patients having Covid-19 related symptoms were shown to have statistically significantly higher mean age compared to the ones who did not have any symptoms (p=0.031). No statistically significant relationship was found Covid-19 RT-PCR positivity and the type of treatment administered for HS when categorized as TNF-alpha inhibitor, oral retinoid, topical antibiotic and oral antibiotic group (p>0.05).